2021
DOI: 10.1111/petr.13977
|View full text |Cite
|
Sign up to set email alerts
|

Is donation after circulatory determination of death feasible for pediatric patients in italy?

Abstract: The imbalance between supply and demand of organs affects the pediatric population while size constraints make the organ match more difficult: every year in Europe especially young children die on waiting lists before they receive a transplant. 1 At the time of this writing, in Italy there were around 240 children waiting for a solid organ transplant with a total waiting list mortality that reached 3,3% in 2019. 2 The pediatric waiting list also risks to be lengthened in 2020 due to the new COVID-19 emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…DCC requires a brief observation period after cessation of circulatory function (hands off), which is generally accepted as a minimum of 2–5 min. Spanish legislation requires a “hands off” time of 5 min, although legislation in countries such as Italy requires periods of up to 20 min to confirm 2,3,18,19 . This heterogeneity, in our opinion and that of other authors, highlights the need to develop standardized protocols for pediatric and neonatal donation after DCC 3 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…DCC requires a brief observation period after cessation of circulatory function (hands off), which is generally accepted as a minimum of 2–5 min. Spanish legislation requires a “hands off” time of 5 min, although legislation in countries such as Italy requires periods of up to 20 min to confirm 2,3,18,19 . This heterogeneity, in our opinion and that of other authors, highlights the need to develop standardized protocols for pediatric and neonatal donation after DCC 3 …”
Section: Discussionmentioning
confidence: 79%
“…Spanish legislation requires a "hands off" time of 5 min, although legislation in countries such as Italy requires periods of up to 20 min to confirm. 2,3,18,19 This heterogeneity, in our opinion and that of other authors, highlights the need to develop standardized protocols for pediatric and neonatal donation after DCC. 3 The informed consent of the legal guardians is required for the donation procedure, but also to perform ante mortem procedures if necessary, such as cannulation of central lines or administration of heparin, aimed at improving the viability of the recovered organs after DCC donation.…”
Section: Donation Procedures and Legal Aspects Of Neonatal Donationmentioning
confidence: 85%
“…Different factors such as ethical, cultural, and logistical factors may account for this discrepancy. A retrospective study conducted by our group to evaluate the impact of a potential pDCDD program on a pediatric intensive care unit (PICU) of a tertiary University Hospital found that pDCDD might have increased organ donation by 20% over an 8‐year period [10]. This finding confirms that pDCDD is a viable option for Italy, even if the Italian law requires a 20‐min no‐touch period to declare death based on cardiocirculatory criteria.…”
Section: Introductionmentioning
confidence: 73%
“…12 In addition, a recent study estimated an active paediatric DCD programme could increase potential donations by 20%. 14 Therefore, there are recurrent missed opportunities for donation for both donors and recipients in Canadian PICUs.…”
Section: Introductionmentioning
confidence: 99%
“…Although most paediatric deaths occur in the PICU,3 13 a 2019 survey showed that several Canadian PICUs did not offer DCD 12. In addition, a recent study estimated an active paediatric DCD programme could increase potential donations by 20% 14. Therefore, there are recurrent missed opportunities for donation for both donors and recipients in Canadian PICUs.…”
Section: Introductionmentioning
confidence: 99%